Lupus and the Lungs: The Assessment and Management of Pulmonary Manifestations of Systemic Lupus Erythematosus - Amarnani, Raj; Yeoh, Su-Ann; Denneny, Emma K.; Wincup, Chris (Frontiers in Medicine, 2021)
Pulmonary manifestations of systemic lupus erythematosus (SLE) are wide-ranging and debilitating in nature. Previous studies suggest that anywhere between 20-90% of patients with SLE will be troubled by some form of respiratory involvement throughout the course of their disease. This can include disorders of the lung parenchyma (such as interstitial lung disease and acute pneumonitis), pleura (resulting in pleurisy and pleural effusion), and pulmonary vasculature (including pulmonary arterial hypertension, pulmonary embolic disease and pulmonary vasculitis), whilst shrinking lung syndrome is a rare complication of the disease. Furthermore, the risks of respiratory infection (which often mimic acute pulmonary manifestations of SLE) are increased by the immunosuppressive treatment that is routinely used in the management of lupus. Although these conditions commonly present with a combination of dyspnea, cough and chest pain, it is important to consider that some patients may be asymptomatic with the only suggestion of the respiratory disorder being found incidentally on thoracic imaging or pulmonary function tests. Treatment decisions are often based upon evidence from case reports or small cases series given the paucity of clinical trial data specifically focused on pulmonary manifestations of SLE. Many therapeutic options are often initiated based on studies in severe manifestations of SLE affecting other organ systems or from experience drawn from the use of these therapeutics in the pulmonary manifestations of other systemic autoimmune rheumatic diseases. In this review, we describe the key features of the pulmonary manifestations of SLE and approaches to investigation and management in clinical practice.